Strengthening Christian Values In The Formation Of Adolescent Identity At Gloria Sentani High School - E Pandi, Seprianti; S. Gainau, Markus; Kabanga, Lewi; E.A.Y.Karetji, Novalia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Youth are the hope for the future, but behind this hope lie challenges that may alter the course of today's youth. The students of SMTK Gloria Sentani face challenges that are feared to shake their faith, leading to a degradation of their beliefs. The purpose of this Community Service (PkM) is to strengthen the Christian values of the youth, particularly the students of SMTK Gloria Sentani, in defining their identity to carve out a brighter future. The methods used in this PkM include observation-interviews, lectures-discussions, and the preparation of accountability reports packaged in the form of scientific articles such as national journals. The results achieved include an understanding and cognitive maturity regarding the concept of the